Catalyst-free "click" functionalization of polymer brushes preserves antifouling properties enabling detection in blood plasma - Parrillo, Viviana; de Los Santos Pereira, Andres; Riedel, Tomas; Rodriguez-Emmenegger, Cesar (Analytica chimica acta, 2017)
Progress in biosensors for clinical detection critically relies on modifications of the transducer surface to prevent non-specific adsorption from matrix components (i.e. antifouling) while supporting biomolecular recognition elements to capture the analyte. Such combination of properties presents a significant challenge. Hierarchically structured polymer brushes comprising an antifouling polymer bottom block and a functionalizable top block are proposed as a promising strategy to achieve this goal. We employed the catalyst-free strain-promoted alkyne-azide cycloaddition (SPAAC) "click" reaction to biofunctionalize antifouling polymer brushes without impairing their resistance to fouling. The functionalization was performed on the side chains along the top polymer block or only on the end-groups of the polymer brush. The immobilized amounts of bioreceptors (streptavidin followed by biotin-conjugated proteins) and the resistance to fouling from blood plasma of the surfaces obtained were evaluated via surface plasmon resonance. The end group functionalization approach resulted in very low immobilization of bioreceptor. On the other hand, the side group modification of a top polymer block led to immobilization of 83% of a monolayer of streptavidin. Following binding of a biotin-conjugated antibody (66 ng cm-2) the functionalized layer was able to reduce the fouling from undiluted human blood plasma by 89% in comparison with bare gold. Finally, the functionalized hierarchical polymer brushes were applied to the label-free detection of a model analyte in diluted human blood plasma, highlighting the potential for translation to medical applications.
Keywords: Affinity optical biosensors; adsorpce; Antibodies, Immobilized; Streptavidin; povrchové vlastnosti; Fouling; imobilizační protilátky; krevní plazma; Click chemistry; Biofouling; Surface Plasmon Resonance; streptavidin; Polymers; Biotin; Surface Properties; Humans; biotin; Blood plasma; povrchová plasmonová rezonance; polymery; Plasma; Click Chemistry; Adsorption; lidé; bioznečištění; click chemie